2020
DOI: 10.3390/s20113230
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistance Sensing of Epoxy Curing Using an Embedded Carbon Nanotube Yarn

Abstract: Curing effects were investigated by using the electrical response of a single carbon nanotube yarn (CNTY) embedded in an epoxy resin during the polymerization process. Two epoxy resins of different viscosities and curing temperatures were investigated, varying also the concentration of the curing agent. It is shown that the kinetics of resin curing can be followed by using the electrical response of an individual CNTY embedded in the resin. The electrical resistance of an embedded CNTY increased (~9%) after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 44 publications
(90 reference statements)
5
19
0
Order By: Relevance
“…During the temperature programs, specimens were equilibrated for 15 min at RT in stabilization zone (S). In order to evaluate the signal noise level, the signal to noise ratio (SNR) of the fractional change in electrical resistance was calculated according to [10]:…”
Section: Experimental Setup For Curing and Cyclic Thermoresistive Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…During the temperature programs, specimens were equilibrated for 15 min at RT in stabilization zone (S). In order to evaluate the signal noise level, the signal to noise ratio (SNR) of the fractional change in electrical resistance was calculated according to [10]:…”
Section: Experimental Setup For Curing and Cyclic Thermoresistive Characterizationmentioning
confidence: 99%
“…In addition, the high porosity of the CNTYs may promote infiltration of liquids between the CNT bundles affecting the stiffness, toughness, and electrical conductivity of the yarn by separating the adjacent CNT bundles and increasing the contact electrical resistance [3,[7][8][9]. It was observed that C 2021, 7, 60 2 of 14 the thermoresistive properties of the embedded CNTY strongly depend on the chemical structure of the polymeric matrix, temperature range, porosity, and capillary diffusion of polar liquids [3,8,[10][11][12][13][14][15]. Rodríguez-Uicab et al [10] investigated the effect of the curing kinetics of epoxy resins with different viscosities on the thermoresistive response of the CNTY monofilament composites at different curing temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain responses of curing stress have been studied by scientists by using carbon fibers [ 17 , 18 , 19 , 20 ], glass fibers [ 21 ], and carbon nanotube yarn [ 22 ]. For example, Y. Huang et al used Raman spectroscopy to study the residual stress in carbon fiber/epoxy resin composites and made it clear that this technology is an excellent scientific tool for determining the residual stress in composites [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Y. Huang et al used Raman spectroscopy to study the residual stress in carbon fiber/epoxy resin composites and made it clear that this technology is an excellent scientific tool for determining the residual stress in composites [ 23 ]. Omar Rodríguez-Uicab et al have investigated the curing effects and development of residual stresses during epoxy resin curing through the electrical response of a single carbon nanotube yarn embedded in the epoxy polymer [ 22 ]. These landmark works boost the development of multifunctional smart materials integrated into structural composites, and have made extraordinary contributions to the study of resin curing kinetics.…”
Section: Introductionmentioning
confidence: 99%